The Concept of Historical Heuristics and Its Application in the Era of Artificial Intelligence - Usman Hadi,; DH, Achmad Zuhdi; Sya'ie, Akhmad Najibul Khairi (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines heuristics, which play a crucial role in historical research methodology. It also explores the benefits and challenges of heuristics in the era of Artificial Intelligence (AI), using the case study of Kiai Dermodjojo’s messianic movement in Nganjuk in 1907 CE. The research employs a qualitative descriptive method, utilizing a literature review technique. The results of this study indicate that heuristics play an irreplaceable role and form the foundation of historical research methodology. The steps of heuristics consist of activities ranging from exploration and identification to the classification of historical sources. Furthermore, a deep understanding of heuristics will also facilitate historians in distinguishing between primary, secondary, and tertiary sources. Meanwhile, in the case study of Kiai Dermodjojo’s messianic movement in Nganjuk in 1907, this study demonstrates that the collection of colonial archives, sources, oral traditions, and artifacts requires the meticulous application of heuristics. On the other hand, the presence of AI can indeed facilitate the heuristic process, although the use of AI also carries the risk of algorithmic bias. This study concludes that AI can be used as a tool to assist historians in the heuristic stage, without replacing the role of historians in historical research methodology. However, a balance must still be maintained between the use of AI and comprehensive scrutiny by researchers when conducting heuristics, so that the resulting research findings are credible and truly scientific.